2007
DOI: 10.1093/europace/eum017
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of rhythm variation during spontaneous cardioinhibitory neurally-mediated syncope. Implications for RDR pacing optimization: an ISSUE 2 substudy

Abstract: Cardioinhibitory neurally-mediated reflex varies widely from a few seconds to some minutes. In our data the total duration was <2 min. Optimal RDR programming, being potentially able to anticipate the detection of the cardioinhibitory reflex by a few seconds, could provide an increase in benefit for cardiac pacing therapy in prevention of syncope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…Some patients with neurocardiogenic syncope have underlying sinus bradycardia and associated high vagal tone. Furthermore, the premonitory rate drop prior to syncope can be rather prolonged, with a total duration of the cardioinhibitory reflex lasting 85 seconds (range 47-116 seconds) (116). An atrial (AAI) pacemaker should not be used in an individual who may have episodic transient AV block due to augmented parasympathetic activation.…”
Section: Neurocardiogenic Syncopementioning
confidence: 99%
“…Some patients with neurocardiogenic syncope have underlying sinus bradycardia and associated high vagal tone. Furthermore, the premonitory rate drop prior to syncope can be rather prolonged, with a total duration of the cardioinhibitory reflex lasting 85 seconds (range 47-116 seconds) (116). An atrial (AAI) pacemaker should not be used in an individual who may have episodic transient AV block due to augmented parasympathetic activation.…”
Section: Neurocardiogenic Syncopementioning
confidence: 99%
“…AV block during neurocardiogenic reflex is rare, although it has been documented during vasovagal and situational syncope. 75,76 AV block provoked by tilt test represents the cardioinhibitory component of the neurocardiogenic reflex which is less frequent than sinus arrest, sinoatrial block, or sinus bradycardia (vagal stimulation on sinoatrial node usually predominates). Zysko et al reported an incidence of 5.2% of complete AV block in patients with positive tilt test, 77 similar to what had been previously found.…”
Section: Vagally Induced Atrioventricular Blockmentioning
confidence: 99%
“…The ILR is implanted subcutaneously in the left hemithorax with automatic and patient-activated ECGdocumentation modes available on most devices. Many studies have shown its value in detection of infrequent arrhythmias [39][40][41] . Current guidelines suggest ILR implantation for unexplained syncopes.…”
Section: The Implantable Loop Recordermentioning
confidence: 99%